PROBLEMS WITH CLEAN WATER SOURCES FOR COASTEL COMMUNITIES IN KUALA LANGSA VILLAGE, ACEH PROVINCE - Susi Mulianti Lubis; Riska Tia Pratiwi; Inka Farahdina; Shally Rezeki (Jurnal Biologi Sains dan Kependidikan, 2022)
Public perception, clean water, PDAM